2011
DOI: 10.1007/s11434-011-4769-4
|View full text |Cite
|
Sign up to set email alerts
|

Power law and small world properties in a comparison of traffic city networks

Abstract: We analyze the statistical properties of the urban public bus networks of two cities (Beijing and Chengdu) in China. To this end, we present a comprehensive survey of the degree distribution, average path length, and clustering of both networks. It is shown that both networks exhibit small world behavior and are hierarchically organized. We also discuss the differences between the statistical properties displayed by the two networks. In addition, we propose a weight distribution approach to study the passenger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
(53 reference statements)
0
4
0
1
Order By: Relevance
“…The presence of more hubs in the Beijing network yielded a smaller γ as compared to Chengdu; while both showed large clustering coefficients and small characteristic path lengths. The location of bus stops in a similar fashion in both the cities have led to a hierarchical structure, which is denoted by a power-law behaviour (with nearly same exponents) between the degree strength (characterizing the passenger flows) and clustering coefficient [53,54].…”
Section: Studies On Bus Transport Networkmentioning
confidence: 99%
“…The presence of more hubs in the Beijing network yielded a smaller γ as compared to Chengdu; while both showed large clustering coefficients and small characteristic path lengths. The location of bus stops in a similar fashion in both the cities have led to a hierarchical structure, which is denoted by a power-law behaviour (with nearly same exponents) between the degree strength (characterizing the passenger flows) and clustering coefficient [53,54].…”
Section: Studies On Bus Transport Networkmentioning
confidence: 99%
“…Traditional modeling approaches to illness propagations, such as COVID-19, assume an exponential growth ( Chen et al, 2020 ; Liang, 2020 ; Liu et al, 2020 ; Pinter et al, 2020 ; Santosh, 2020 ; Shinde et al, 2020 ). However, increasing evidence shows that human dynamics have power-law properties ( Barabási, 2007 ; Grabowski, 2007 ; Ma et al, 2011 ; Muchnik et al, 2013 ). In fact, recent work has shown that multiple measurements of human activity follow allometric properties such as , where N is the number of individuals and w a metric of activity ( Bettencourt et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional modeling approaches to illness propagations, such as COVID-19, assume an exponential growth (11)(12)(13)(14)(15)(16). However, increasing evidence shows that human dynamics and clustering has power-law properties (17)(18)(19)(20). In fact, recent work has shown that multiple measurements of human activity follow allometric properties such as ∝ , where N is the number of individuals and w a metric of activity (21).…”
Section: Introductionmentioning
confidence: 99%